Normas DRIS para rendimento de grão e teor de óleo da cultura da soja, cultivada na planalto médio do Rio Grande do Sul - Castamann, Alfredo (2009)
Among others factors, the nutritional diagnosis of plants and growing medium can be used to improve the yield of agricultural crops. The nutrient sufficient range (SR) approach has been the leaf diagnosis methods most used to evaluate the nutritional condition of plants. This method does not consider the relation between the nutrients analyzed in the leaf tissue, but it can be evaluated by using DRIS. In order to use this last method, it is required to know the binary rations between the nutrients concentrations, the DRIS norms, which change with the crop, soil and whether conditions as well as the variable evaluated as harvested product. The DRIS norms have not been established for the most soybean regions of Brazil, including the state of Rio Grande do Sul (RS), which limit the application of this method. The general objective of this work was to insert the DRIS method for the nutritional diagnosis of soybean crops, related to the grain yield and the grain oil concentration, for the soil and whether conditions of Planalto Médio Region, RS state, Brazil, in 2008 and 2009. The specific objectives were to generate the DRIS norms for soybean crops, related to the grain yield and the grain oil concentration; to compare the DRIS norms obtained in 2008 with the obtained in 2009; to evaluate the correlation between the DRIS index and the grain yield and the grain oil concentration; and to compare the DRIS and SR diagnoses. The leaf and grain samples analyzed were sampled at farmer production and UPF research fields, in Planalto Médio Region, RS, Brazil. The total macro and micronutrients content (except molybdenum and chloride), of the third trifoliolate leaf fully expanded, sampled at R2 (full-bloom) growth stage, were analyzed. The DRIS norms were obtained by relating the binary values of the nutrients rations with the grain yield and oil contents, of the reference population, by using Beaufils approach. The DRIS index values were evaluated according to the fertilization response potential criteria, while the nutrient leaf content was evaluated according to the sufficient range criteria, proposed by Tecnologias (2006), besides the references values suggested by the official research of Santa Catarina and RS states. It was possible to generate the DRIS norms with the grain yield and grain oil results. The norms changed with the year evaluated. Plants with higher values of Ca and Mg DRIS indexes showed higher grain yield, while the opposite was found with higher values of K and B indexes. The grain oil content was higher with higher values of B, Ca, Mg, and S DRIS indexes, while the opposite was found with higher values of K, N, and P indexes. The diagnostic obtained with this method was more comprehensive than the obtained with the SR, with both response variable, grain yield and grain oil content